Los conocimientos, actitudes y prácticas en el ejercicio de la sexualidad y las conductas de riesgo sexual de los estudiantes de primer año de bachillerato paralelo m, del colegio Beatriz Cueva de Ayora, 2020-2021. - Balcázar Macas, Henrry Fabricio (2022)
The research called, THE KNOWLEDGE, ATTITUDES AND PRACTICES IN THE EXERCISE OF SEXUALITY AND THE SEXUAL RISK BEHAVIORS OF THE FIRST YEAR STUDENTS OF PARALLEL HIGH SCHOOL M, OF THE BEATRIZ CUEVA DE AYORA COLLEGE, 2020-2021. Research with a quantitative, descriptive approach, nonexperimental design, cross-correlational section; the Sexual Knowledge and Practices Questionnaire, the Adolescent Sexual Attitude Test, and the Risky Sexual Behavior Index Scale were applied to the sample of 24 students. The results of the questionnaire show that those surveyed have medium-level knowledge about sexuality; As for the sexual attitude, they have an unfavorable attitude; In relation to sexual risk behaviors, it was found that they have medium levels of risky sexual behaviors. It is concluded that those investigated maintain low levels of knowledge of sexuality, unfavorable attitudes towards sexuality and risk behaviors; It is recommended to consider the psychoeducational proposal of sexual education through the use of group dynamics techniques to strengthen knowledge, attitudes and practices in the exercise of sexuality and prevent risk behaviors.